2020
DOI: 10.1021/acs.energyfuels.9b04183
|View full text |Cite
|
Sign up to set email alerts
|

FeII(EDTA)–NO Reduction by Mn Powder in Wet Flue Gas Denitrification Technology Coupled with Mn2+ Recycling: Performance, Kinetics, and Mechanism

Abstract: Fe II (EDTA) solution has been considered an efficient option in wet flue gas denitrification, whereas the generated Fe II (EDTA)−NO restricts its wide application, suggesting that Fe II (EDTA)−NO reduction is the key to this process. This work investigated the performance, kinetics, and mechanism of Fe II (EDTA)−NO reduction by Mn powder coupled with manganese ion (Mn 2+ ) recovery. We initially studied the performance of Fe II (EDTA)−NO reduction with respect to the major influencing factors (i.e., the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Over the years, wet denitrification of flue gas has been extensively investigated by various researchers, leading to significant achievements [26][27][28][29][30]. It has many advantages such as simple process equipment, short equipment operation cycle, low operating temperature, low energy consumption, good removal effect, and low treatment cost [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, wet denitrification of flue gas has been extensively investigated by various researchers, leading to significant achievements [26][27][28][29][30]. It has many advantages such as simple process equipment, short equipment operation cycle, low operating temperature, low energy consumption, good removal effect, and low treatment cost [26].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, wet denitrification of flue gas has been extensively investigated by various researchers, leading to significant achievements [26][27][28][29][30]. It has many advantages such as simple process equipment, short equipment operation cycle, low operating temperature, low energy consumption, good removal effect, and low treatment cost [26]. In particular, the complexation absorption method is a promising research field among many wet denitrification technologies and opens a new chapter of wet combined desulfurization and denitrification [27].…”
Section: Introductionmentioning
confidence: 99%
“…Complex NO can be chemically reduced by a series of reducing agents, including sulfites, bisulfite, urea, reductive metals (Fe, Mn, Zn), sodium hydrosulfite, coal pyrite, and sulfide . These reduction processes usually generate byproducts that are difficult to recover, leading to secondary pollution challenges for the chemical method.…”
Section: Introductionmentioning
confidence: 99%
“…Among many iron chelates, iron­(II) ethylenediaminetetraacetic acid (Fe­(II)­(EDTA)) has attracted much attention because of its high NO absorption capacity ( K = 1.5 × 10 6 M –1 at 25 °C) and kinetics ( k = 1.7 × 10 8 M –1 s –1 at 25 °C). , However, the initial high NOx removal efficiency could not be maintained in the presence of O 2 (typically 4–7% in the flue gas) because Fe­(II)­EDTA is easily oxidized by O 2 , and the resultant Fe­(III)­EDTA has little binding affinity toward NO. ,, To solve this critical problem, iron­(II) thiochelates, notably Fe­(II)­(DMPS) 2 , in which DMPS denotes 2,3-bis­(sulfanyl)­propane-1-sulfonic acid (otherwise called 2,3-dimercaptopropane-1-sulfonic acid), have emerged as less O 2 -sensitive alternatives. In the previous study, Fe­(II)­(DMPS) 2 showed a prolonged high NO removal efficiency in comparison to Fe­(II)­EDTA on account of high O 2 resistance . Besides, this iron­(II) thiochelate has a higher equilibrium constant for the nitrosylation reaction (eq ) than other iron­(II) chelates and thus has a greater NO absorption capacity …”
Section: Introductionmentioning
confidence: 99%